IRA Mauritanie: Legacy and Innovation in the Anti-slavery Fight in Mauritania - Giuseppe Maimone (Antropologia, 2020)
The fight against slavery in Mauritania is more than 40 years old, but over the past decade it has become more prominent, driven by IRA Mauritanie (Initiative pour la résurgence du mouvement abolitionniste en Mauritanie), a non-violent organization led by the abolitionist leader Biram Dah Abeid. Drawing on historical analysis and qualitative research, this article enriches the existing literature on IRA Mauritanie’s ideology and activism by showing how it melds elements of innovation with some of the characteristics of previous Mauritanian anti-slavery organizations. Specifically, it demonstrates how, in its claims of a Haratin identity (freed slaves and their descendants of black origin), IRA combines new fighting strategies with claims of ethnic autonomy made by previous anti-slavery movements. Contrary to the common view that IRA is an unprecedented threat to the unity of Mauritania, this article argues that while it follows in some of its predecessors’ footsteps it is developing new fighting strategies.